Diversity of Terrestrial Molluscs in Ngoc Son-Ngo Luong Nature Reserve, Hoa Binh Province (Mollusca: Gastropoda) - Sang, Do Duc; Thanh Son, Nguyen; Thi Hue, Nguyen; Wayne Van Devender, Robert (VNU Journal of Science: Earth and Environmental Sciences, 2021)
Ngoc Son-Ngo Luong Nature Reserve composes of a large variety of natural habitats, such as limestone forest, limestone karsts, caves and isolated limestone hills. Therefore, this area is expected to have a high species diversity, especially for the terrestrial molluscs. A total of 56 species was recorded, of which 12 were recorded in Hoa Binh Province for the first time. The data on terrestrial molluscs in this study could be considered as a scientific basis to carry on systematic research.